2014
DOI: 10.1117/12.2060725
|View full text |Cite
|
Sign up to set email alerts
|

Optical design and characterization of an advanced computational imaging system

Abstract: We describe an advanced computational imaging system with an optical architecture that enables simultaneous and dynamic pupil-plane and image-plane coding accommodating several task-specific applications. We assess the optical requirement trades associated with custom and commercial-off-the-shelf (COTS) optics and converge on the development of two low-cost and robust COTS testbeds. The first is a coded-aperture programmable pixel imager employing a digital micromirror device (DMD) for image plane per-pixel ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…Structured illumination architectures ( Fig. 1(d)) use an SLM at a conjugateimage plane in the illumination path and follow the same generalized mathematical model as the IPC architecture [27]. Structured illumination microscopy techniques can even reach video rate imaging with better than diffraction limited resolution [28,29].…”
Section: Compressive Imaging Architecturesmentioning
confidence: 99%
“…Structured illumination architectures ( Fig. 1(d)) use an SLM at a conjugateimage plane in the illumination path and follow the same generalized mathematical model as the IPC architecture [27]. Structured illumination microscopy techniques can even reach video rate imaging with better than diffraction limited resolution [28,29].…”
Section: Compressive Imaging Architecturesmentioning
confidence: 99%
“…The second strategy is based on passive imaging and therefore does not need a specialized light source. Within this category, representative techniques are parallel streak imaging using a tilted lenslet array [200], temporal pixel multiplexing [201], compressed ultrafast photography [27], coded aperture compressive temporal imaging [202], programmable pixel compressive imaging [13], and smart pixel imaging with computational-imaging arrays [203, 204]. …”
Section: Snapshot Multidimensional Imaging Implementations and Appmentioning
confidence: 99%
“…By contrast, smart pixel imaging (SPI) with computational-imaging arrays [203, 204] transfers this encoding process to the digital domain by using a digital-pixel focal plane array, thereby minimizing the signal-to-noise loss caused by physical encoding elements, such as the DMD in CUP and P2C2, and the absorption mask in CACTI. In SPI, each detector pixel can be modulated by a time-varying, pseudo-random, and dual-binary signal (−1,1 or 1,0) at a rate up to 100 MHz.…”
Section: Snapshot Multidimensional Imaging Implementations and Appmentioning
confidence: 99%
“…where 16 ] T . In this work, to make the symbols clear and understandable, subscript is used to indicate the pixel position and superscript is for the number of the low-resolution MWIR image.…”
Section: Introductionmentioning
confidence: 99%
“…The compressed sampling process can be speeded up by using a focal plane array-based (FPA) sensor instead of the photodetector in SPC. Although the FPA CI systems have been implemented in visible [15,16] and short-wave infrared (SWIR) wavebands [17], comparatively few systems are implemented in MWIR. To our knowledge, only two experimental studies in the area of MWIR FPA CI are reported: Mahalanobis of Lockheed Martin built the first MWIR FPA CI system [18], which is a "merged-type", and we built a "separate-type" system [19].In spite of the acceleration of imaging speed, FPA CI has brought new challenges to the quality of reconstructed high-resolution images.…”
mentioning
confidence: 99%